Cell-mediated immunity to Herpes simplex in humans: lymphocyte cytotoxicity measured by 51-Cr release from infected cells. - Russell, A S (1975)
We assessed cell-mediated immunity to herpes simplex virus type 1 antigen in patients suffering from recurrent cold sores and in a series of healthy controls. Paradoxically, all those subject to recurrent herpetic infections had, without exception, evidence of cell-mediated immunity to herpes antigens. This was demonstrated by lymphocyte transformation and specific 51Cr release from infected human amnion cells after incubation with peripheal blood mononuclear cells. Where performed, skin tests with herpes antigen were also positive. In addition, serum from these patients specifically sensitized herpesvirus-infected cells to killing by nonimmune, control mononuclear cells. These tests were negative in the control patients except in a few cases, and it is suggested that these latter may be the asymptomatic herpesvirus carriers previously recognized or that they may have experienced a genital infection.